STUDI TENTANG PRESTASI BELAJAR SISWA DI SMAN 7 TANGERANG MENURUT KARAKTERISTIK : GENDER, USIA, SIKAP, LINGKUNGAN - muhammad roffi tamammul Huda; khusaini khusaini; sri lestari (Universitas Islam Syekh Yusuf, 2020)
ABSTRACTThis study aims to determine differences in learning achievement based on gender, age, attitude and environment. This research is in the form of quantitative method used in this study is a comparative approach or average difference test. The population used in this study were students of class XII SMAN 7 Tangerang City in 2019/2020 with 125 students. The sample used is a saturated sample, which means that the entire population is used a sample with the same amount of 125. Data collection techniques in this study were questionnaire or questionnaire and documentation for gender, age, attitude and environment. In research using the Mann Whitney test and One Way Anova. The results of this study indicate that there are differences in learning achievement on attitudes. While there is no difference in gender, age and environment.Keywords : Learning Achievement, Gender, Age, Attitude, Environtment